Drivers of E-Commerce Success in Java Island: Implications for Indonesia's Digital Economy - Rosmeli, Rosmeli; Yossinomita, Yossinomita; Ekasari, Novita; Friyani, Rita; Alvaro, Rakan (Integrated Journal of Business and Economics (IJBE), 2025)
E-commerce in Indonesia, particularly on Java Island, has shown rapid development, contributing significantly to national digital transactions. This study aims to analyze the factors influencing the growth of e-commerce on Java Island during the 2015–2023 period. The research employs a panel data regression model, examining variables such as communication expenditure, population size, the number of BTS towers, mobile phone ownership, and the number of e-commerce actors.  The key findings reveal that communication expenditure, mobile phone ownership, and the number of e-commerce actors significantly influence digital transactions. These findings underscore the importance of enhancing digital infrastructure, improving internet access, and empowering digital MSMEs to support the growth of e-commerce in Indonesia. Promoting e-commerce growth by improving internet infrastructure in areas with poor connectivity is a crucial first step the government can take to enhance internet access equity across Java Island.